2019
DOI: 10.1103/physrevb.99.075425
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation in Mie-resonant dielectric nanoparticles made of noncentrosymmetric materials

Abstract: We develop a multipolar theory of second-harmonic generation (SHG) by dielectric nanoparticles made of noncentrosymmetric materials with bulk quadratic nonlinearity. We specifically analyze two regimes of optical excitation: illumination by a plane wave and single-mode excitation, when the laser pump drives the magnetic dipole mode only. Considering two classes of nonlinear crystalline solids (dielectric perovskite material and III-V semiconductor), we apply a symmetry approach to derive selection rules for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 59 publications
0
82
0
Order By: Relevance
“…According to [21,[25][26][27][28], the field E, which satisfies the Helmholtz equation ∇ 2 E + ε ω c 2 E = 0 with frequency ω in a medium with dielectric susceptibility ε, can be expanded into a series of vector spherical harmonics N p r mn ( √ ε ω c , r) (electric) and M p r mn ( √ ε ω c , r) (magnetic), introduced in [21,29]. They correspond to the electric field of electric and magnetic multipoles of the nth arXiv:1812.02988v3 [physics.optics]…”
Section: Derivation Of Selection Rulesmentioning
confidence: 99%
See 3 more Smart Citations
“…According to [21,[25][26][27][28], the field E, which satisfies the Helmholtz equation ∇ 2 E + ε ω c 2 E = 0 with frequency ω in a medium with dielectric susceptibility ε, can be expanded into a series of vector spherical harmonics N p r mn ( √ ε ω c , r) (electric) and M p r mn ( √ ε ω c , r) (magnetic), introduced in [21,29]. They correspond to the electric field of electric and magnetic multipoles of the nth arXiv:1812.02988v3 [physics.optics]…”
Section: Derivation Of Selection Rulesmentioning
confidence: 99%
“…The superscript (3) means that the harmonic corresponds to a diverging wave [21]. In [29], using the multipole expansion of the Green's function [28,[30][31][32][33] it was shown that the coefficients D p i p r mn are proportional to the integral of the scalar product of the induced SH polarization P 2ω (r) =χ (2) E ω (r)E ω (r) and the vector harmonic with indices p i , p r , m, n over the nanoparticle volume: (2) E ω (r)E ω (r)] dV .…”
Section: Ordermentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the nanoparticles of larger sizes comparable to the wavelength can also be considered that will increase the efficiency of SPDC process. This way, one should take into account the excitation of the higher-order multipolar components in the nanoparticle and their consequent decay into the other modes preserving particular symmetry rules typical for the second-order nonlinear processes [25,26]. This renders the considered scheme as a general recipe for the symmetry-based nonlinear generation of N00N-states with nanoparticles.…”
Section: Introductionmentioning
confidence: 99%